Childhood Abuse and Intimate Partner Violence Victimization Among Filipina and South Asian Women in the United States - Akiko Kamimura; Maziar M. Nourian; Nushean Assasnik; Kimiya Nourian; Kathy Franchek-Roa (Mary Ann Liebert, 2020)
Background: Intimate partner violence (IPV) is a common form of interpersonal violence and impacts the health and well-being of victims over their lifetime. Many victims of IPV experience multiple types of victimization throughout their lives, often starting in childhood. The prevalence of IPV victimization of women varies among different race/ethnic groups. The purpose of this project is to examine childhood abuse among Filipina and South Asian women living in the United States who had experienced IPV. Methods: Data were extracted from Lifecourse Experiences of Intimate Partner Violence and Help-Seeking among Filipina, Indian, and Pakistani Women: Implications for Justice System Responses 2007?2009 (San Francisco, CA) (ICPSR 29682). Data were collected from 143 women (87 Filipina and 56 South Asian (i.e., Indian or Pakistani) aged between 18 and 60 years who had been a victim of IPV and lived in the United States. Results: Although both Filipina and South Asian women who had experienced IPV reported a high prevalence of childhood abuse, Filipina women reported a higher prevalence than South Asian women. South Asian women were more likely to have first experienced IPV at a younger age and sought some form of IPV services as compared with Filipina women. The factors associated with experiencing all the types of IPV victimization included younger age at the first physical IPV victimization experience and higher educational attainment. Conclusions: Future research should examine the cumulative victimization of childhood abuse and IPV among Asian populations and its impact on health.